Biosensing of microcystins in water samples; recent advances - Kordasht, Houman Kholafazad; Hassanpour, Soodabeh; Baradaran, Behzad; Nosrati, Rahim; Hashemzaei, Mahmoud; Mokhtarzadeh, Ahad; la Guardia, Miguel de (Biosensors & bioelectronics, 2020)
Safety and quality of water are significant matters for agriculture, animals and human health. Microcystins, as secondary metabolite of cyanobacteria (blue-green algae) and cyclic heptapeptide cyanotoxin, are one of the main marine toxins in continental aquatic ecosystems. More than 100 microcystins have been identified, of which MC-LR is the most important type due to its high toxicity and common detection in the environment. Climate change is an impressive factor with effects on cyanobacterial blooms as source of microcystins. The presence of this cyanotoxin in freshwater, drinking water, water reservoir supplies and food (vegetable, fish and shellfish) has created a common phenomenon in eutrophic freshwater ecosystems worldwide. International public health organizations have categorized microcystins as a kind of neurotoxin and carcinogen. There are several conventional methods for detection of microcystins. The limitations of traditional methods have encouraged the development of innovative methods for detection of microcystins. In recent years, the developed sensor techniques, with advantages, such as accuracy, reproducibility, portability and low cost, have attracted considerable attention. This review compares the well-known of biosensor types for detection of microcystins with a summary of their analytical performance.
Keywords: biosenzitivní techniky; Animals; mikrocystiny; ekosystém; voda; Humans; Ecosystem; Reproducibility of Results; lidé; reprodukovatelnost výsledků; Water; zvířata; Microcystins; Biosensing Techniques